Development of iso-octane fuel processor system for fuel cell applications - Moon, Dong Ju; Ryu, Jong Woo; Yoo, Kye Sang; Sung, Dae Jin; Lee, Sang Deuk (ELSEVIER SCIENCE BV, 2008)
An iso-octane fuel processor system with three different reaction stages, autothermal reforming (ATR) reaction of iso-octane, high temperature shift (HTS) and low temperature shift (LTS) reactions, was developed for applications in a fuel cell system. Catalytic properties of the prepared Ni/Fe/MgO/Al2O3 and Pt-Ni/CeO2 or molybdenum carbide catalysts were compared to those of commercial NiO/CaO/Al2O3 and Cu/Zn/Al2O3 catalysts for ATR and LTS reaction, respectively. It was found that the prepared catalysts formulations in the fuel processor system were more active than those of the commercial catalysts. As the exit gas of iso-octane ATR over the Ni/Fe/MgO/Al2O3 catalyst was passed through Fe3O4-Cr2O3 catalyst for HTS and Mo2C or Pt-Ni/CeO2 catalyst for LTS reaction, the concentration of CO in hydrogen-rich stream was reduced to less than 2400 ppm. The results suggest that the iso-octane fuel processor system with prepared catalysts can be applied to PEMFC system when a preferential partial oxidation reaction is added to KIST iso-octane reformer system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: POWERED VEHICLES APPLICATIONS; WATER-GAS SHIFT; PARTIAL OXIDATION; CATALYST